Comparative physiological and root proteome analyses of two sorghum varieties responding to water limitation - Goche, Tatenda (Sci Rep, 2020)
When exposed to drought stress many plants reprogram their gene expression to activate adaptive biochemical and physiological responses for survival. However, most of the well-studied adaptive responses are common between drought-sensitive and drought-tolerant species, making it difficult to identify the key mechanisms underpinning successful drought tolerance in crops. We developed a sorghum experimental system that compares between drought-sensitive (ICSB338) and enhanced drought-tolerant (SA1441) varieties. We show that sorghum activates a swift and robust stomatal shutdown to preserve leaf water content when water stress has been sensed. Water uptake is enhanced via increasing root cell water potential through the rapid biosynthesis of predominantly glycine betaine and an increased root-to-shoot ratio to explore more soil volume for water. In addition to stomatal responses, there is a prompt accumulation of proline in leaves and effective protection of chlorophyll during periods of water limitation. Root and stomatal functions rapidly recover from water limitation (within 24 h of re-watering) in the drought-tolerant variety, but recovery is impaired in the drought-sensitive sorghum variety. Analysis of the root proteome revealed complex protein networks that possibly underpin sorghum responses to water limitation. Common and unique protein changes between the two sorghum varieties provide new targets for future use in investigating sorghum drought tolerance.